THE EFFECTIVENESS OF TEACHING VOCABULARY BY USING PICTURES OF COMUNICATION AT STATE PRIMARY SCHOOL 023905 BINJE UTARA - Siti Rakiyah (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2018)
English is noticed as one of international languages which is very common to be used by people from different region and country to communicate each other. Nevertheless, the ability to use this language should de developed during age of children at primary school. Students are often trapped by the very old-fashioned way of learning. They get bored even when they are not learning it. It makes students find that English is more difficult than it actually is. Vocabulary is one of the language components that have to be taught to the students in learning as a  foreign language. To improvethe students’ vocabulary, the teacher can use many media. By using picture as media, the student can learn easily and interestingly.The aim of this research is to find out whether there is a significant effect of teaching vocabulary using picture to improve students’ vocabulary. In this research, the writer took 30 students of the fifth-grade of State Primary School 023905 Binje Utara in the academic year 2016/2017 as the sample. For collecting the data, the instruments were used quantitative data (vocabulary test) and qualitative data. Based on the data, it was found that the students vocabulary score improved from orientation test, cycle I test, and cycle II test. In the orientation test, the mean of the students’score was 60%, in cycle I test, the mean of the students’score was 75%, and in cycle II test, the mean of the students’score was 89.28%. it was found that teaching speking through picture can improve the students interest in vocabulary. It can be concluded that teaching vocabulary through picture is effective in teaching vocabulary and English teachers should try this strategy.The teacher uses the variety of teaching methods in teaching learning process in order to get the higher achievement of the students